Radon isotopes as tracers of climate-sensitive subsurface connectivity in Antarctic permafrost - L. Ruggiero; A. Sciarra; A. Mazzini; F. Florindo; G. Wilson; C. Mazzoli; P. Tuccimei; G. Galli; L. Tositti; A. Zappi; J. Anderson; L. Davidson; et al. (Environmental Research, 2026)

Development of magadiite-whey hybrid composites for the adsorptive removal of xylenol orange dye - S. Benkhatou; F. Ouazani; Y. Chergui; A. Djelad; A. Mokhtar; M. Bouchekara; M. Sassi (International Journal of Environmental Science and Technology, 2025)

Impact of Terrestrial Weather on the Space Weather of the Ionosphere-Thermosphere: Initial Results from a NASA Living with a Star Focused Science Topic - J. Oberheide; D. Aggarwal; B. Bergsson; S. Chakraborty; S. Debchoudhury; M. Dhadly; F. Gasperini; L. Goncharenko; V. L. Harvey; C. Heale; P. Inchin; J. Li; et al. (Surveys in Geophysics, 2025)
The ionosphere-thermosphere (IT) is a convergence point of energy and processes that interconnect Earth’s atmosphere with space. Processes generated by terrestrial weather in the lower atmosphere (i.e., troposphere and stratosphere, altitudes less than ~ 50 km) are recognized by the scientific community as sources of variability in both the structure and composition of the IT. Exposed to persistent wave forcing from terrestrial weather sources and solar and magnetic forcing, the IT is a domain of compelling scientific inquiry that connects thermodynamics, fluid dynamics, electrodynamics and plasma physics. Predicting its space weather is of significant national interest for space situation awareness including the very low earth orbit as the new frontier of space operations. Advancing the understanding of whole atmosphere interconnections between terrestrial and space weather requires coordinated modeling and observational efforts across different spatial and temporal scales. Toward this goal, the National Aeronautics and Space Administration (NASA), through the living with a star (LWS) program, established in 2022 a focused science topic (FST) to study the problem from various angles. In this manuscript we report on the vision, goals and status of the ongoing FST “Impact of Terrestrial Weather on the Ionosphere—Thermosphere”. Initial results show bigger impacts on the IT than hitherto thought and help to more clearly define the state-of-the-art in the context of future NASA missions such as EZIE, DYNAMIC and GDC.

Integrative morphological, cytogenetic and molecular characterization of the Andean climbing catfish Astroblepus mindoensis ( Regan , 1916) ( Siluriformes:Astroblepidae ) - Mauro Nirchio; Claudio Oliveira; Marcelo de Bello Cioffi; Francisco M. C. Sassi; Francisco Provenzano Rizzi; Santiago Wladimir Núñez Benavides; Alison Jazmín Calderón Berrones; Juan Francisco Rivadeneira Romero; Geize Aparecida Deon; Mariana Kuranaka; Jonathan Santiago Valdiviezo‐Rivera; Julio C. Carrión Olmedo; et al. (Journal of Fish Biology, 2025)
Astroblepus species, commonly known as Andean climbing catfish, exhibit a unique challenge in species delimitation, leading to ongoing taxonomic debates. Here we report data on Astroblepus mindoensis , a vulnerable species endemic to Ecuador, obtained by an integrative approach that includes cytogenetic analysis, molecular identification of the specimens, and recording of morphological and morphometric characters useful for species diagnosis. Thus, this study aimed to associate the karyotype data of the specimens analyzed with morphological and molecular characters, improving and expanding the existing taxonomic information, thus contributing to the systematics of the species. Our morphology results, unlike Regan's original description, which is brief and ambiguous, provide a more detailed morphometric and meristic description. Molecular phylogenetic reconstruction and genetic distance based on a fragment of the cytochrome c oxidase subunit I ( COI ) showed that our samples constitute a well‐supported and monophyletic clade within the A. grixalvii species complex. The cytogenetic analysis identified distinct chromosomal markers, including a single cluster of major ribosomal genes (on chromosome pair 3) and of minor ribosomal genes (on chromosome pair 12) with their localization differing from those reported in other Astroblepus species analyzed. Additionally, the presence of a heteromorphic chromosome pair in males suggests the presence of an XX/XY sex‐determination system that has not been identified in other congeneric species. Further investigation is necessary to determine if these chromosomes are associated with the accumulation of repeated sequences, as typically occurs with sex chromosomes, and to assess their presence in other species of the genus.

Surprising concentrations of hydrogen and non-geological methane and carbon dioxide in the soil - G. Etiope; G. Ciotoli; E. Benà; C. Mazzoli; T. Röckmann; M. Sivan; A. Squartini; T. Laemmel; S. Szidat; N. Haghipour; R. Sassi (Science of The Total Environment, 2024)

Artificial intelligence for tunnel boring machine penetration rate prediction - A. Flor; F. Sassi; M. La Morgia; F. Cernera; F. Amadini; A. Mei; A. Danzi (Tunnelling and Underground Space Technology, 2023)

Isolating the impact of COVID-19 lockdown measures on urban air quality in Canada - Rabab Mashayekhi; Radenko Pavlovic; Jacinthe Racine; Michael D. Moran; Patrick M. Manseau; Annie Duhamel; Ali Katal; Jessica Miville; David Niemi; Si Jun Peng; Mourad Sassi; Debora Griffin; et al. (Air Quality, Atmosphere & Health, 2021)
We have investigated the impact of reduced emissions due to COVID-19 lockdown measures in spring 2020 on air quality in Canada’s four largest cities: Toronto, Montreal, Vancouver, and Calgary. Observed daily concentrations of NO 2 , PM 2.5 , and O 3 during a “pre-lockdown” period (15 February–14 March 2020) and a “lockdown” period (22 March–2 May 2020), when lockdown measures were in full force everywhere in Canada, were compared to the same periods in the previous decade (2010–2019). Higher-than-usual seasonal declines in mean daily NO 2 were observed for the pre-lockdown to lockdown periods in 2020. For PM 2.5 , Montreal was the only city with a higher-than-usual seasonal decline, whereas for O 3 all four cities remained within the previous decadal range. In order to isolate the impact of lockdown-related emission changes from other factors such as seasonal changes in meteorology and emissions and meteorological variability, two emission scenarios were performed with the GEM-MACH air quality model. The first was a Business-As-Usual (BAU) scenario with baseline emissions and the second was a more realistic simulation with estimated COVID-19 lockdown emissions. NO 2 surface concentrations for the COVID-19 emission scenario decreased by 31 to 34% on average relative to the BAU scenario in the four metropolitan areas. Lower decreases ranging from 6 to 17% were predicted for PM 2.5 . O 3 surface concentrations, on the other hand, showed increases up to a maximum of 21% close to city centers versus slight decreases over the suburbs, but O x (odd oxygen), like NO 2 and PM 2.5 , decreased as expected over these cities.

Physiological responses and expression of sugar associated genes in faba bean (Vicia faba L.) exposed to osmotic stress - Emna Ghouili; Khaled Sassi; Moez Jebara; Yassine Hidri; Rim Nefissi Ouertani; Yordan Muhovski; Salwa Harzalli Jebara; Mohamed El Ayed; Souhir Abdelkarim; Oumaima Chaieb; Selim Jallouli; Fatma Kalleli; et al. (Physiology and Molecular Biology of Plants, 2021)

Differential expression of miRNAs related to angiogenesis and adipogenesis in subcutaneous fat of obese and nonobese women - Aline S. Gasparotto; Diego O. Borges; Marina G. M. Sassi; Adriana Milani; Darwin L. Rech; Marcia Terres; Pedro B. Ely; Mauricio J. Ramos; Nelson G. Meihnardt; Vanessa S. Mattevi (Molecular Biology Reports, 2019)

An outbreak in intravenous drug users due to USA300 Latin-American variant community-acquired methicillin-resistant Staphylococcus aureus in France as early as 2007 - M. Sassi; B. Felden; M. Revest; P. Tattevin; Y. Augagneur; P.-Y. Donnio (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Genetic variability in Tunisian populations of faba bean (Vicia faba L. var. major) assessed by morphological and SSR markers - Feten Rebaa; Ghassen Abid; Marwa Aouida; Souhir Abdelkarim; Ibtissem Aroua; Yordan Muhovski; Jean-Pierre Baudoin; Mahmoud M’hamdi; Khaled Sassi; Moez Jebara (Physiology and Molecular Biology of Plants, 2017)

Genetic Relationship and Diversity Analysis of Faba Bean (Vicia Faba L. var. Minor) Genetic Resources Using Morphological and Microsatellite Molecular Markers - Ghassen Abid; Dominique Mingeot; Sripada M. Udupa; Yordan Muhovski; Bernard Watillon; Khaled Sassi; Mahmoud M’hamdi; Fatma Souissi; Khediri Mannai; Fathi Barhoumi; Moez Jebara (Plant Molecular Biology Reporter, 2015)

Identification and characterization of drought stress responsive genes in faba bean (Vicia faba L.) by suppression subtractive hybridization - Ghassen Abid; Yordan Muhovski; Dominique Mingeot; Bernard Watillon; André Toussaint; Guy Mergeai; Mahmoud M’hamdi; Khaled Sassi; Moez Jebara (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

The addition of entropy-based regularity parameters improves sleep stage classification based on heart rate variability - M. Aktaruzzaman; M. Migliorini; M. Tenhunen; S. L. Himanen; A. M. Bianchi; R. Sassi (Medical & Biological Engineering & Computing, 2015)

The dimensionality of ecological networks - Anna Eklöf; Ute Jacob; Jason Kopp; Jordi Bosch; Rocío Castro‐Urgal; Natacha P. Chacoff; Bo Dalsgaard; Claudio de Sassi; Mauro Galetti; Paulo R. Guimarães; Silvia Beatriz Lomáscolo; Ana M. Martín González; et al. (Ecology Letters, 2013)
How many dimensions (trait‐axes) are required to predict whether two species interact? This unanswered question originated with the idea of ecological niches, and yet bears relevance today for understanding what determines network structure. Here, we analyse a set of 200 ecological networks, including food webs, antagonistic and mutualistic networks, and find that the number of dimensions needed to completely explain all interactions is small (

Plant‐mediated and nonadditive effects of two global change drivers on an insect herbivore community - Claudio de Sassi; Owen T. Lewis; Jason M. Tylianakis (Ecology, 2012)
Warmer temperatures can alter the phenology and distribution of individual species. However, differences across species may blur community‐level phenological responses to climate or cause biotic homogenization by consistently favoring certain taxa. Additionally, the response of insect communities to climate will be subject to plant‐mediated effects, which may or may not overshadow the direct effect of rising temperatures on insects. Finally, recent evidence for the importance of interaction effects between global change drivers suggests that phenological responses of communities to climate may be altered by other drivers. We used a natural temperature gradient (generated by elevation and topology), combined with experimental nitrogen fertilization, to investigate the effects of elevated temperature and globally increasing anthropogenic nitrogen deposition on the structure and phenology of a seminatural grassland herbivore assemblage (lepidopteran insects). We found that both drivers, alone and in combination, severely altered how the relative abundance and composition of species changed through time. Importantly, warmer temperatures were associated with biotic homogenization, such that herbivore assemblages in the warmest plots had more similar species composition than those in intermediate or cool plots. Changes in herbivore composition and abundance were largely mediated by changes in the plant community, with increased nonnative grass cover under high treatment levels being the strongest determinant of herbivore abundance. In addition to compositional changes, total herbivore biomass more than doubled under elevated nitrogen and increased more than fourfold with temperature, bearing important functional implications for herbivores as consumers and as a prey resource. The crucial role of nonnative plant dominance in mediating responses of herbivores to change, combined with the frequent nonadditive (positive and negative) effects of the two drivers, and the differential responses of species, highlight that understanding complex ecosystem responses will benefit from multifactor, multitrophic experiments at community scales or larger.

Understanding osmotic stress tolerance in leaves and nodules of two Phaseolus vulgaris cultivars with contrasting drought tolerance - Sameh Sassi; Samir Aydi; Esther M. Gonzalez; Cesar Arrese-Igor; Chedly Abdelly (Symbiosis, 2010)

Physiological determinants of Yo-Yo intermittent recovery tests in male soccer players - Ermanno Rampinini; Aldo Sassi; Andrea Azzalin; Carlo Castagna; Paolo Menaspà; Domenico Carlomagno; Franco M. Impellizzeri (European Journal of Applied Physiology, 2010)

Differences in the Crack Resistance of Interstitial, Osteonal and Trabecular Bone Tissue - L. P. Mullins; V. Sassi; P. E. McHugh; M. S. Bruzzi (Annals of Biomedical Engineering, 2009)

Determination of the chemical composition of ulvan, a cell wall polysaccharide from Ulva spp. (Ulvales, Chlorophyta) by FT-IR and chemometrics - A. Robic; D. Bertrand; J.-F. Sassi; Y. Lerat; M. Lahaye (Journal of Applied Phycology, 2009)

Tolerance of common bean to long-term osmotic stress is related to nodule carbon flux and antioxidant defenses: evidence from two cultivars with contrasting tolerance - Sameh Sassi; Esther M. Gonzalez; Samir Aydi; Cesar Arrese-Igor; Chedly Abdelly (Plant and Soil, 2008)

Detoxification of olive mill wastewaters by Moroccan yeast isolates - A. Ben Sassi; N. Ouazzani; G. M. Walker; S. Ibnsouda; M. El Mzibri; A. Boussaid (Biodegradation, 2008)

Antiviral activity of some Tunisian medicinal plants against Herpes simplex virus type 1 - A. Ben Sassi; F. Harzallah-Skhiri; N. Bourgougnon; M. Aouni (Natural Product Research, 2008)

Level ground and uphill cycling ability in elite female mountain bikers and road cyclists - F. M. Impellizzeri; T. Ebert; A. Sassi; P. Menaspà; E. Rampinini; D. T. Martin (European Journal of Applied Physiology, 2007)

POTOS: a portable topographic system for measuring inaccessible muddy creek areas - Darío R. Minkoff; Gerardo M. E. Perillo; Daniel E. Perez; Silvio D. Maraschín; Maximiliano Sassi (Wetlands Ecology and Management, 2007)

Simulations of anthropogenic change in the strength of the Brewer–Dobson circulation - N. Butchart; A. A. Scaife; M. Bourqui; J. de Grandpré; S. H. E. Hare; J. Kettleborough; U. Langematz; E. Manzini; F. Sassi; K. Shibata; D. Shindell; M. Sigmond (Climate Dynamics, 2006)

Prediction of time to exhaustion from blood lactate response during submaximal exercise in competitive cyclists - A. Sassi; S. M. Marcora; E. Rampinini; P. Mognoni; F. M. Impellizzeri (European Journal of Applied Physiology, 2006)